المسؤولية الجنائية عن تفشي فايروس كورونا: دراسة تحليلية في ضوء القوانين والعراقية - البرزنجي، كشاو معروف سيده; علي، ديمن حسين; الشوانى، نوزاد أحمد ياسين (جامعة كركوك - كلية القانون والعلوم السياسية, 2021)
تعد تفشي فايروس كورونا أخطر كارثة إنسانية قد تؤدي بأرواح الملايين من البشر، إذا لم يتم السيطرة على هذا الوباء الذي يهاجم الإنسان في واحد من أهم أجهزة جسمه ألا وهي الجهاز التنفسي، بالرغم من اهتمام كافة الأوساط العالمية منها الدولية والوطنية لما له من آثار وخيمة على صحة الإنسان وحياته لأنه قد يؤدي إلى الموت، ولقد دلت الإحصائيات الصادرة عن منظمة الصحة العالمية بتزايد الأعداد من المصابين والمتوفين يومياً. وتزامناً مع الأوساط الطبية كان لزاماً علينا البحث في المسؤولية الجنائية لتفشي فايروس كورونا وبيان النصوص العقابية في قانون العقوبات العراقي رقم 111 لسنة 1969 المعدل وقانون الصحة العامة رقم 89 لسنة 1981 المعدل رقم وحتى قانون المرور رقم 8 لسنة 2019 المعدل.
The Corona virus outbreak is the most serious humanitarian catastrophe that could lead to the lives of millions of people, if the control of this epidemic that attacks a person in one of the most important organs of his body is not the respiratory system, Despite the interest of all global circles, including the international and national levels, because of its disastrous effects on human health and life, as it may lead to death, statistics issued by the Health Organization have shown Global is increasing numbers of injured and deceased daily. In conjunction with the medical community, we had to research the criminal responsibility of the Corona virus outbreak and clarify punitive texts in the Penal Code. Iraqi No. 111 of 1969 as amended and Public Health Law No. 89 of 1981 amended and even Traffic Law No. 8 of 2019 amended.
Keywords: القوانين والتشريعات -- المسؤولية الجنائية -- فايروس كورونا -- الأوبئة والأمراض -- الوقاية والعلاج